Analisis Penerapan Aplikasi Transformasi Digital PLN Mobile Guna Meningkatkan Kinerja Karyawan dan Pelayanan Terhadap Kepuasan Pelanggan di PT PLN (Persero) Unit Pelaksana Pelayanan Pelanggan (UP3) Surabaya Barat - Pertiwi, Nadilla Putri; Nirawati, Lia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
PT PLN (Persero) UP3 Surabaya Barat is a PLN unit tasked with distributing electricity. As a customer service implementation unit, PLN UP3 Surabaya Barat also provides maximum service in implementing customer service. The purpose of this research is to determine the application of the PLN Mobile application in improving employee performance and service towards customer satisfaction. The method used is qualitative research using interviews and literature review observations. Interviews were conducted with employees of PLN UP3 Surabaya Barat and several customers who use the PLN Mobile application. For PLN UP3 Surabaya Barat employees, the PLN Mobile application is very helpful in performance because it is effective in serving customers and saves time. The existence of these digital applications is useful in facing current digitalization competition. Apart from that, the assessment of the PLN Mobile application also received a positive response from customers, because it has features that are easy to access and use and also provide great efficiency in carrying out electricity transactions, complaints and submitting new installations or additional power.